The Differential Regional Effects of Monetary Policy - Carlino, Gerald; DeFina, Robert (The Review of Economics and Statistics, 1998)
This paper examines whether monetary policy has similar effects across regions in the United States. Impulse response functions from an estimated structural vector autoregression reveal a core of regions—New England, Mideast, Plains, Southeast, and the Far West— that respond to monetary policy changes in ways that closely approximate the U.S. average response. Of the three noncore regions, one (Great Lakes) is noticeably more sensitive to monetary policy changes, and two (Southwest and Rocky Mountains) are found to be much less sensitive. A state-level version of the model is estimated and used to provide evidence on the channels for monetary policy.